Moderate-and-vigorous physical activity from adolescence to adulthood and subclinical atherosclerosis in adulthood: prospective observations from the European Youth Heart Study. Issue 2 (13th April 2013) - Ried-Larsen, Mathias; Grøntved, Anders; Kristensen, Peter Lund; Froberg, Karsten; Andersen, Lars Bo
Abstract : Aim: To investigate the independent associations between mean exposure to or the change in moderate-and-vigorous physical activity (PA) from adolescence to adulthood and subclinical atherosclerosis in adulthood. Methods: This was a prospective cohort study among Danish boys and girls (N=277) followed for up to 12 years (age 15.7 (0.4) at baseline) enrolled in the European Youth Heart Study. PA intensity was objectively measured at baseline and follow-up, and ultrasonography was performed on the Carotid arteries at follow-up. Data on carotid intima-media thickness (cIMT), Carotid Compliance and Young's Elastic Modules were used as outcome measures. Results: In the multivariable analyses (adjusted for personal—lifestyle and demographic factors) the mean exposure to moderate-and-vigorous PA from adolescence to adulthood was negatively associated with Young's Elastic Modules (β=−0.001×10 3  kPa (95% CI −0.0015 to −0.0002), p=0.02) and positively associated with Carotid Compliance (β=0.004 mm 2  kPa −1 (95% CI 0.002 to 0.008), p=0.003) and cIMT (β=0.0003 mm (95% CI 0.00001 to 0.0007), p=0.013). Increases in moderate-and-vigorous PA from adolescence to adulthood were negatively associated with Young's Elastic Modules in adulthood (β=−0.00007×10 3  kPa (95% CI −0.0012 to −0.0001), p=0.01). Furthermore, participants with the largest decline in moderate-and-vigorous PA from adolescence to adulthood displayed significantly less compliant arteries compared with the remaining sample (p<0.05). Conclusions: High mean exposure to moderate-and-vigorous PA levels and increases herein were independently associated with lower levels of carotid arterial stiffness in adulthood.